1989
DOI: 10.1111/j.1095-8649.1989.tb03029.x
|View full text |Cite
|
Sign up to set email alerts
|

The immune response of wild rainbow trout, Salmo gairdneri Richardson, to naturally acquired plerocercoid infections of Diphyllobothrium dendriticum (Nitzsch, 1824) and D. ditremum (Creplin, 1825)

Abstract: Natural infections of rainbow trout with two species ofDiphyllobothrium result in a host inflammatory response encapsulating the plerocercoid. The encapsulating cyst, observed by light and electron microscopy, comprises leucocytes, fibroblasts and collagenous connective tissue and is infiltrated with a blood vascular network. An indirect immunofluorescence technique and enzyme‐linked immunosorbant assay (ELISA) have shown that specific antibodies are elicited by the fish host to these Diphyllobothrium spp. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 34 publications
(27 reference statements)
1
61
1
Order By: Relevance
“…The significance of this observation is not entirely clear, as it is possible that, rather than representing a specific reaction to Anisakis spp., they might reflect a physiological state of the fish. Persistent inflammation and massive recruitment of granular cells in the intestinal tissue of helminth-infested salmonids has been previously described (Murray 1972, Sharp et al 1989, Ferguson 2006, but similarly, a massive degranulation of EGCs followed by an acute inflammatory reaction can be induced by the injection of hydrocortisone (Reite 1997). The histological analysis of samples from fish that had been in the freshwater for weeks or months showed that EGCs were not predominant anymore or were completely absent.…”
Section: Asp Ay821749 Tc--cgta Ta-cagttt--gtgtgatc-tatgt--caa Cgcaamentioning
confidence: 95%
“…The significance of this observation is not entirely clear, as it is possible that, rather than representing a specific reaction to Anisakis spp., they might reflect a physiological state of the fish. Persistent inflammation and massive recruitment of granular cells in the intestinal tissue of helminth-infested salmonids has been previously described (Murray 1972, Sharp et al 1989, Ferguson 2006, but similarly, a massive degranulation of EGCs followed by an acute inflammatory reaction can be induced by the injection of hydrocortisone (Reite 1997). The histological analysis of samples from fish that had been in the freshwater for weeks or months showed that EGCs were not predominant anymore or were completely absent.…”
Section: Asp Ay821749 Tc--cgta Ta-cagttt--gtgtgatc-tatgt--caa Cgcaamentioning
confidence: 95%
“…Mast cells may play an important role in the mechanisms of inflammatory response because they express a number of functional proteins, including antimicrobial peptides that act against a broad spectrum of pathogens [249][250][251][252][253].…”
Section: Immune Cells In Fish Skinmentioning
confidence: 99%
“…Coscia & Oreste, 1998, 2000 and tapeworms (e.g. Kennedy & Walker, 1969 ;Sharp, Pike & Secombes, 1989). There has also been intensive speculation on how humoral factors in the immune response of fish are involved in protection.…”
Section: Introductionmentioning
confidence: 99%
“…There has also been intensive speculation on how humoral factors in the immune response of fish are involved in protection. Such mechanisms as effects on parasite fecundity (Grayson et al 1995), binding to glandular secretions and surface structures (Sharp et al 1989 ;Williams & Hoole, 1995), mediation of leucocyte adherence (Hoole & Arme, 1986 ;Whyte et al 1990), induction of parasite migration out of the fish (Clark & Dickerson, 1997) and mediation of complementinduced lysis (Saeij, De Vries & Wiegertjes, 2003) have been proposed. In contrast, the mechanisms by which fish helminth parasites evade and/or suppress the immune response has not been extensively considered although Hoole & Arme (1983) have speculated that host proteins may be acquired on the surface of the plerocercoid of Ligula intestinalis and used to evade the immune response in its cyprinid hosts.…”
Section: Introductionmentioning
confidence: 99%